(untitled) (Scientific journal of the Fergana State University, 2025)
Physical exercise activities are related to the functional capabilities of our body parts due to their specific characteristics. The article discusses the situation where a student, unaware of the level of functional capacity of their body parts, imposes excessive physical demands on themselves, which can lead to a reluctance to engage in activities.